Improving the rheometry of heterogeneous bituminous binders through experimental and numerical procedures - Giancontieri, Gaspare (2020)
Nowadays, heterogeneous materials are widely used for an extensive range of engineering applications and rheological measurements are intensively adopted for their development and quality control. These materials are often mixtures with different densities that exhibit improved engineering performance as well as a reduced environmental impact thanks to the addition of special modifiers. The success of these family of materials is very much linked to the accurate control of their properties during production and storage. This is the case of Heterogeneous Bituminous Binders (HBBs), such as crumb rubber modified bitumens (CR-MBs), used for asphalt mixtures for road pavements. Asphalt technologists are used to monitoring, in the range of 100°C to 200°C, the rotational viscosity of HBBs during product development and quality control. This exercise is usually carried out in a laboratory using a rotational viscometer. Nevertheless, due to their complexity, the characterisation of these materials may be challenging as some common procedures used to characterise their properties may not be adequate. Indeed, during rotational viscosity testing the sample may undergo a number of changes, such as phase separation, sedimentation, agglomeration, viscoelastic effects etc., leading to the here-defined sample instability which in turn provides misleading results. This is the reason behind the necessity of efficient mixing during viscosity measurements of HBBs. To overcome the above-mentioned issues, this study introduces a combined experimental-numerical approach aimed to improve the rheometry of HBBs. To do that, a computational fluid dynamics (CFD) model was developed to assess whether the CFD is a tool capable to reproduce the observations of a laboratory campaign on HBBs. Numerical simulations confirmed the experimental results and proved sample instability during rotational testing of heterogeneous materials, hence the need of a new device able to reduce the level of heterogeneity within the sample. Based on the numerical remarks, a deep literature investigation on mixing devices efficiency was carried out and a new geometry identified: the dual helical ribbon (DHR). The novel device was designed and verified by means of numerical modelling then manufactured in stainless steel. Once the DHR was realised, the combined experimental-numerical approach was used to provide evidence of the above-mentioned phenomena. The experimental campaign was performed, by recording eventual differences in rotational viscosity readings of HBBs while using both a standard spindle (SC-27) and the DHR as impellers of the rotational viscometer. In parallel, a tailored numerical model provided advanced visual aids aimed to better understanding the fundamentals behind the instability phenomena. Finally, an improved laboratory application based upon the adoption of the DHR for real-time monitoring of HBBs’ properties during manufacturing and hot storage is presented. Results of this combined numerical and experimental approach proved first that the CFD is a powerful tool able to reproduce the laboratory observations but also to offer a deeper insight into the measuring chamber by providing useful information about the sample instability. Laboratory campaign offered a further evidence that when dealing with HBBs the standard setup for rotational viscosity measurements does not appear to be adequate. Sample instability has been understood as correlated to deficient mixing, hence the DHR has shown to be beneficial in resolving the issue. Additionally, the procedure to perform quality control of HBBs has provided a set of practical conclusions to optimise full-scale production with regards to the type of modifier and the storage temperature. Therefore, the adoption of this geometry is strongly recommended for high-temperature viscosity measurements of CR-MB and potentially for any other HBB.